Crystal structure of Tam41 cytidine diphosphate diacylglycerol synthase from a Firmicutes bacterium. (29th December 2021) - Kimura, Keisuke; Kawai, Fumihiro; Kubota-Kawai, Hisako; Watanabe, Yasunori; Tomii, Kentaro; Kojima, Rieko; Hirata, Kunio; Yamamori, Yu; Endo, Toshiya; Tamura, Yasushi
Abstract: Translocator assembly and maintenance 41 (Tam41) catalyses the synthesis of cytidine diphosphate diacylglycerol (CDP-DAG), which is a high-energy intermediate phospholipid critical for generating cardiolipin in mitochondria. Although Tam41 is present almost exclusively in eukaryotic cells, a Firmicutes bacterium contains the gene encoding Tam41-type CDP-DAG synthase (FbTam41). FbTam41 converted phosphatidic acid (PA) to CDP-DAG using a ternary complex mechanism in vitro . Additionally, FbTam41 functionally substituted yeast Tam41 in vivo . These results demonstrate that Tam41-type CDP-DAG synthase functions in some prokaryotic cells. We determined the crystal structure of FbTam41 lacking the C-terminal 18 residues in the cytidine triphosphate (CTP)-Mg 2+ bound form at a resolution of 2.6 Å. The crystal structure showed that FbTam41 contained a positively charged pocket that specifically accommodated CTP-Mg 2+ and PA in close proximity. By using this structure, we constructed a model for the full-length structure of FbTam41 containing the last a-helix, which was missing in the crystal structure. Based on this model, we propose a molecular mechanism for CDP-DAG synthesis in bacterial cells and mitochondria. Graphical Abstract: